Absorbing and developing qualified fighter pilots : the role of the advanced simulator - Marken, Richard S., 1946- (RAND Project Air Force, 2007)
What does an individual need to be considered an experienced fighter pilot? The current formal definition is based on how many flying hours a person has, but in practice, the question is more complex and sometimes subjective because an individual requires different kinds of experience for combat positions and staff positions. The authors surveyed training experts to discover practical bases for judgments about the experience needed for different jobs. For flying positions, they found that time in advanced simulators is now also considered to be an important component of experience. Upgrade levels (say, from wingman to flight lead) and types of sorties flown are factors for both flying and staff positions. The results suggest that it is time for the Air Force to consider revising the view that a pilot is experienced or not is based only on the number of hours flown. The Air Force needs to measure and credit different types of experience-including time spent in advanced simulator systems-when revising its definitions of pilot experience.